TOEFL Scores of English Department Students Cenderawasih University - Budi Rahayu (Center of Language and Cultural Studies [CLCS], 2020)
This study aims at comparing the TOEFL scores of the English Department students at the Faculty of Teacher Training and Education, Cenderawasih University. The questions that need to be answered are first, whether there are any differences of TOEFL scores amongst English department students from different semesters. Secondly, whether there are any different scores between male and female students, third between the students with different learning backgrounds, and forth between students with different levels of interest in English. The participants are the students of semester 2, semester 4, semester 6, and semester 8, commencing in the academic year 2017/2018. TOEFL prediction test was given to the participants to get the scores. The scores of each variable were then compared by the application of ANOVA and t-test. The result of this study can give a picture of how English teaching can be improved.